GAMBARAN PENGETAHUAN PREMENOPAUSE TENTANG PERUBAHAN FISIK DALAM MENGHADAPI MASA MENOPAUSE DI DUSUN MANNYOI DESA TAMANNYELENG KECAMATAN BAROMBONG KAB. GOWA - Agustina Ningsi; Sitti Mukarramah; Sukmayanti Sukmayanti (Media Keperawatan:Politeknik Kesehatan Makassar, 2020)
Premenapause Knowledge Overview About Physical Period Facing Menopause Period In Mannyoi Village Tamannyeleng Village Barombong District Gowa Regency 2018. (guided by HJ Sitti Mukarramah and Agustina Ningsih)Changes that occur during menopause, women experience a peak complaint while in the post-menopausal phase of this period lasts 6-7 years after menopause. At this time estrogen levels after the low point in accordance with the state of the art and accompanied by the deterioration of body condition. This study aims to determine the characteristics of respondents and description of premenopausal knowledge about physical changes in the face of menopause In Mannyoi Village Tamannyeleng Village District Barombong Gowa District. Samples were taken from primary data, all mothers aged 40 to 55 years old in Mannyoi Village Tamannyeleng Village Barombong District of Gowa regency that fit the criteria in sampling, during the period of February to May 2018, the type of research is descriptive with the method used is through a questionnaire with cross sectional approach, with a sample size of 50 respondents.Characteristics of respondents based on the level of education is elementary education of 41 respondents (82%), SMP of 8 respondents (16%) and the high school education of 1 respondent (2%) and characteristics of respondents by age, 40-49 years age of 37 74%) and age> 50 years at 13 (26%). Good knowledge as many as 34 people (68%), while knowledgeable enough as much as 9 people (18%) and who have less knowledge as much as 7 people (14%). One of the main concerns of mother's knowledge is the intervention of health workers and information from the surrounding community Keywords: Knowledge, PremenopauseReferences: 15 (2006-2017)